IMPLEMENTASI PROGRAM PENGEMBANGAN ANAK USIA DINI HOLISTIK INTEGRATIF (PAUD HI) UNTUK PENINGKATAN KUALITAS SATUAN PENDIDIKAN DI TAMAN KANAK-KANAK AL FASIHI DAY SCHOOL KECAMATAN TEMPE KABUPATEN WAJO - Suhartini; Besse Herlina; Tenri Sau (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe and analyze the implementation of the Holistic Integrative Early Childhood Development (HI-ECD/PAUD HI) program in enhancing the quality of educational units at TK Al Fasih Day School, Tempe District, Wajo Regency. HI-ECD is an approach to early childhood development designed to meet children's diverse and interrelated essential needs simultaneously, systematically, and in an integrated manner. This research employs a qualitative method, with data collected through interviews, observations, and documentation. The findings indicate that the implementation of HI-ECD at TK Al Fasih Day School encompasses services in education, health, nutrition, care, parenting, as well as protection and welfare. Integration strategies are executed through collaboration with relevant agencies, such as community health centers (Puskesmas) and the Social Affairs Office. Supporting factors for this implementation include the commitment of school management and active parental participation, while identified barriers involve limitations in specific health-supporting infrastructure. The implementation of this program has significantly improved the quality of the educational unit, as evidenced by enhanced management standards, fulfillment of student nutrition, and the achievement of school accreditation.